Broadband measurement of true transverse relaxation rates in systems with coupled protons: application to the study of conformational exchange. Issue 34 (3rd August 2021) - Kiraly, Peter; Dal Poggetto, Guilherme; Castañar, Laura; Nilsson, Mathias; Deák, Andrea; Morris, Gareth A.
Abstract : Existing methods for measuring transverse relaxation give incorrect results in coupled spin systems. Measuring true relaxation rates extends their utility. Abstract : Accurate measurement of transverse relaxation rates in coupled spin systems is important in the study of molecular dynamics, but is severely complicated by the signal modulations caused by scalar couplings in spin echo experiments. The most widely used experiments for measuring transverse relaxation in coupled systems, CPMG and PROJECT, can suppress such modulations, but they also both suppress some relaxation contributions, and average relaxation rates between coupled spins. Here we introduce a new experiment which for the first time allows accurate broadband measurement of transverse relaxation rates of coupled protons, and hence the determination of exchange rate constants in slow exchange from relaxation measurements. The problems encountered with existing methods are illustrated, and the use of the new method is demonstrated for the classic case of hindered amide rotation and for the more challenging problem of exchange between helical enantiomers of a gold(i ) complex.